Effect of Liberalization on Banking Competition - Melanie S. Milo; Gloria O. Pasadilla (Philippine Institute for Development Studies (PIDS), 2005)
The paper analyzes the impact of major policy changes on banking structure, performance and competition, using bank-specific data from 1990-2002. We find that the entry of more market players is correlated with drops in interest spread and profits which, partly, bespeaks of possible dissipation of previous monopoly profits of large commercial banks. We also compute the H-stat based on the Panzar-Rosse methodology and find that, in general, despite the characteristic presence of few, large commercial banks, the sector is fairly competitive, specially in the loan-granting business. Moreover, competition has increased in the latter half of 1990s, primarily due to the presence of more small commercial banks, rather than big banks.
Keywords: 330; competition policy; banking reforms; bank liberalization; h-statistics; Panzar-Rosse methodology; Finanzsystem; Bankenreform; Bankenregulierung; Deregulierung; Wettbewerb; Philippinen